Corrosion of low carbon steel by bacteria, study of its effect on physical properties (fatigue) (Journal of the College of Basic Education, 2022)
He studied the role of biological corrosion caused by the sulfur oxidizing bacteria Thiobacillus and its effect on the physical properties of low carbon steel (0.11%). The research focused on the study of fatigue strength due to its importance in thiooxidans measuring the endurance of materials.Bacteria were obtained from sulfur springs in Hammam Al-Alil (Northern Iraq). These bacteria were isolated on solid thiosulfate medium, then samples were taken from them and the medium was inoculated with themmineral salts in a glass flask